Application For Bankruptcy By Creditors Perspective Of Law Number 37 Of 2004 Concerning Bankruptcy And Suspension Of Debt Payment Obligations(Study of Decision Number 3/Pdt.Sus-Pailit/2021/PN Niaga Jkt. Pst) - Muhammad Nurohim; Yusuf Hanafi; Asmaiyani Asmaiyani (IHSA Institute, 2022)
Settlement of debtors' debts to creditors through the bankruptcy process must meet the elements and requirements in filing an application for bankruptcy. In this case, the law requires that there must be two or more creditors and the non- payment of debts due to at least one creditor. The mechanism for the settlement of debtor assets in the event of bankruptcy is carried out by the Curator through several stages, namely: bankruptcy, verification meeting, making a list of debts and receivables of Bankruptcy, reconciliation and the stage of settlement of bankrupt assets. The basis for the judge's consideration in imposing a bankruptcy decision is in Decision Number 3/Pdt.Sus-Pailit/2021/PN Niaga Jkt. Pst, namely considering whether or not the conditions in the bankruptcy petition are fulfilled by the bankruptcy applicants. Apart from taking into account the circumstances in which the Bankrupt Respondent was proven to have completely failed to pay its due debt to at least one creditor.